THE SECURITY OF PERSONAL DATA IN EUROPEAN UNION SINCE 2018 - Dariusz Brążkiewicz (Rozprawy Społeczne, 2019)
Intensive development of information technology in the early 21st century means that citizens’ personal data is constantly processed using increasingly advanced digital technologies. At the same time, technological development includes more and more areas of a modern man, including administrative, economic and financial areas. In order to maintain and improve security in the field of personal data protection, it is necessary to create new legal solutions. The introduction of unitary supranational solutions in European Union will eliminate or significantly reduce the risks associated with the collection, processing and use of personal data. Responsibility for this security will rest, as it has been until now, on institutions and companies, and professionally prepared employees who supervise or process this data. When the General Data Protection Regulation (GDPR) of the European Union came into force on 25 May 2018, increased protection of personal data will be applied by: increasing the analysis of the risk of personal data processing, accountability of personal data processing, privacy of personal data protection and liability for violation of the provisions on the protection of personal data, including very high financial penalties.